One, No One, and One Hundred Thousand - Marco Improta (Politikon, 2021)
Despite a considerable body of literature on Italian ethnoregionalist parties, scholars of nationalism and regionalism have overlooked southernist parties. This article aims to fill this lacuna by examining Italian southernist parties’ identity and electoral performance from 1945 to 2020. Firstly, it investigates southernist parties according to ideological positioning, autonomist or secessionist nature, and territorial area of origin. Then, by relying on official data, it explores the parties’ electoral performance in national, European, and regional elections. The main findings of the study show that, since the end of World War II, Italian southernist parties: a) have been characterized by a more autonomist rather than secessionist nature; b) have followed the typical patterns of the catch-all party; c) have performed better in regional elections. This article provides preliminary information on southernist parties, paving the way for further research on such political formations.